2013
DOI: 10.1038/hr.2013.80
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine controlled-release 40 mg b.i.d. in Japanese patients with essential hypertension who responded insufficiently to nifedipine controlled-release 40 mg q.d.: a phase III, randomized, double-blind and parallel-group study

Abstract: This phase III, multicenter, randomized, double-blind, parallel-group study compared the efficacy and safety of nifedipine controlled-release (CR) 40 mg twice daily (b.i.d.) and once daily (q.d.) in 325 Japanese patients with essential hypertension uncontrolled with nifedipine CR 40 mg q.d. (ClinicalTrials.gov record: NCT01287260). The primary endpoint was the change from baseline in trough seated diastolic blood pressure (DBP) after 8 weeks. Nifedipine CR 40 mg b.i.d. showed significantly greater reductions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Because of its diuretic-like properties, the SGLT2 inhibitors combined with RAAS inhibitors might contribute to the SBP-lowering effects [19]. RAAS inhibitors were useful for preventing the development of diabetic kidney disease [27] and the guidelines of AHA/ACC and JSH recommend the use of RAAS inhibitors as a first-line drug for hypertensive patients complicated with diabetes [28, 29]. The effects and mechanisms of the combined use of RAAS inhibitors and SGLT2 inhibitors on plasma volume, renal function, and electrolytes should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its diuretic-like properties, the SGLT2 inhibitors combined with RAAS inhibitors might contribute to the SBP-lowering effects [19]. RAAS inhibitors were useful for preventing the development of diabetic kidney disease [27] and the guidelines of AHA/ACC and JSH recommend the use of RAAS inhibitors as a first-line drug for hypertensive patients complicated with diabetes [28, 29]. The effects and mechanisms of the combined use of RAAS inhibitors and SGLT2 inhibitors on plasma volume, renal function, and electrolytes should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a small-scale retrospective study of patients with a poorly controlled essential hypertension despite antihypertensive therapy showed that administration of CR nifedipine at 80 mg per day monotherapy was well tolerated over 24 months of follow-up. 12 A phase III trial of CR nifedipine 80 mg per day monotherapy 13 also demonstrated the short-term efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“… 12 More recently, a phase III trial demonstrated superior antihypertensive efficacy of nifedipine 80 mg per day (40 mg BID) vs nifedipine 40 mg per day in Japanese patients with essential hypertension as monotherapy. 13 Furthermore, administration of 20–40 mg of CR nifedipine in combination with other antihypertensive drugs is effective for the treatment of essential hypertension. 14 , 15 Indeed, treatment guidelines suggest that combination therapy with ⩾2 antihypertensive drugs is often required to achieve BP control, with CCBs being recommended in most of the preferred combinations.…”
Section: Introductionmentioning
confidence: 99%
“…In a pooled analysis of data, lowering sodium intake was shown to be best-targeted at individuals with hypertension who consume high-sodium diets [12]. On the basis of these results, hypertension management guidelines recommend the following: salt intakes of < 5 g/day in Europe [6], < 6 g/day in Japan [8], and sodium intake of < 1500 mg/day (salt intake of < 3. 81 g/day equivalent) in the USA [7].…”
Section: Gene-sodium Interactionmentioning
confidence: 99%
“…The recommendations of hypertension guidelines in major countries consist of the following elements: weight reduction, a healthy diet (dietary patterns characterized by a high consumption of fruit, vegetables, whole grains, legumes, seeds, nuts, fish, low-fat dairy, and a low consumption of meat and sweets), dietary sodium reduction, increasing physical activity, quitting smoking (including avoiding passive smoking), and moderate alcohol consumption (Table 1) [68]. The hypertension guidelines are mostly the same for each country or region, beyond race and culture [9].…”
mentioning
confidence: 99%